Investigation of the reactivity of aminopyridines on C-H activation reaction: a direct route to azaindoles - Martins, Maria Margarida Penhasco (2022)
Azaindoles are relevant heterocyclic aromatic organic compounds that exhibit interesting biological activity. However, the azaindole core is challenging to achieved and most reported methods require the pre-functionalization of substrates. The C–H activation/functionalization reaction is an emergent topic, as organic scientists look at C–H bonds as reactive functional groups in metal-catalyzed reactions, avoiding the pre-functionalization of substrates and resulting in an approach that is less time and cost consuming plus environmentally friendly. C–H activation reactions are scarce regarding azaindole synthesis and, up to date, only two examples can be found in the literature which are restricted to the 7-azaindole isomer. In this project, a methodology to attain the azaindole core through dual intramolecular C–H activation has been developed. For this purpose, very important synthetic intermediates – imines/enamines – have been prepared from C–N cross-coupling reaction of aminopyridines and α-bromostryrene. In an one-pot procedure, this unique C–N cross-coupling/C–H activation reaction allowed to obtain six azaindole structures (I.1–49%, I.2–9%, II.1–37%, III.1–64%, III.2–18%, IV.1–5%), with the first three reported for the first time. Different catalytic systems for C–N cross-coupling and C–H activation reactions have been tested and manipulated in order to obtain the best conditions for each aminopyridine. A different reactivity was observed for each aminopyridine, depending on the presence of substituents and the substitution pattern in the pyridine ring. For the C–N cross-coupling reaction, Pd2dba3/XPhos/t-BuONa (I.1/I.2, III.1/III.2 and IV.1) and Pd2dba3/XantPhos/t-BuONa (II.1) were applied and for the C–H activation reaction Pd(OAc)2/Cu(OAc)2/Cs2CO3 (I.1/I.2) and Pd(OAc)2/Ag2CO3/PivOH (II.1, III.1/III.2 and IV.1). The best yield obtained was for unsubstituted azaindole III.1/III.2, with a total conversion of 82%. Additionally, the addition of silver salts on the C–H activation reaction demonstrated to influence the regioselectivity. Ketone condensation with aminopyridines was tested as an alternative method to obtain the imine/enamine. It was concluded that the condensation reaction wasn’t efficient under the tested reaction conditions and better results might be obtained via a stepwise ketone condensation/C–H activation procedure. Finally, a mechanistic proposal was undertaken based on NMR data, computational calculations and literature.